Perception and factors associated with the possibility of treating patients with COVID-19 in recently graduated physicians at Peru - Loayza-Salvatierra, Natali (2021)
Introduction. Worldwide, including Peru, there is a shortage of human resources to attend for COVID-19 patients, for which reason, newly graduated doctors are being recruited. Material and Methods: Analytical cross-sectional study, using a virtual survey, asked about the possibility of being recruited to care for patients with Coronavirus, as well as other perceptions of this possibility (obtaining a Cronbach's Alpha: 0.86); analytical statistics were obtained. Results: Of 352 respondents, 54% stated that they would accept to be recruited. Multivariate analysis revealed that more fatalistic disease perception takes less be recruited in a hospital (p <0.001); however, if they felt well trained (p <0.001), comfortable supporting in hospitals (p = 0.015), able to provide general care (p <0.001) and could work in a place with many cases (p <0.001); adjusted for two variables. Conclusion: Although there was not a large majority who wanted to be recruited, if this would happen they would have to adapt and they stated that they would be comfortable and trained attending to patients with this pathology.